Cocoa Farmers' Participation in Public and Private Agricultural Extension Delivery in Amenfi Central District, Ghana - Enoch Kwame Tham-Agyekum; Fred Ankuyi; Prince Asiedu; Bright Juantoa; Goddea Asiedu Abourden; John-Eudes Andivi Bakang; Akua Yeboah Oduro-Owusu (CV. AFDIFAL MAJU BERKAH, 2024)
Agricultural extension and knowledge management have become key blocks in driving sustainable food systems and rural development, especially in periods of dealing with the complexities surrounding climate change and sustainable food systems in localised systems. This study assessed cocoa farmers' participation in public and private agricultural extension services in Ghana. Using descriptive and inferential statistics and collecting data from 385 farmers, the study reveals that private extension services stand out in various indices: access to information (3.72), communication (3.96), and support and follow-up (3.45), while public extension services excel in social and environmental impact (3.54), and knowledge transfer (3.86). Intricate extension programme dynamics also reveal a clear preference for private extension in citizen power (23.6% vs. 7.3%), delegated power (33.2% vs. 8.6%), and partnership (39.2% vs. 13.5%). Using the binary probit regression model, this study examines how various socio-economic factors influence farmers' participation in extension programmes. Results indicate that key determinants for participation in public extension include gender, level of education, land size, availability of labour, and access to credit. Conversely, factors influencing participation in private extension programmes include membership in farmer groups, land ownership, land size, the availability of labour, and access to credit. Policymakers and extension workers can make extension services more useful and open to everyone by focusing on these socioeconomic factors and creating programmes that meet the unique needs and limitations of various farmer groups. This will ultimately lead to higher agricultural productivity, better livelihoods, and better rural development.